Hocak teaching materials. - Hartmann, Iren; Marschke, Christian (North American native peoples, past and present., 2010)
This second volume of teaching materials for the Hocak language illuminates the intricacies of the spoken language by showing how the words and grammatical information given in volume 1 are used in actual speech. A range of entire texts is featured, accompanied by a detailed grammatical analysis and a word-by-word, as well as a free-form, translation. Also included are two CDs containing recordings of all texts made for documentary purposes. This volume is an essential aid for fully grasping and practicing the Hocak language today. --Book Jacket.